Evaluating OMEx combustion towards stoichiometric conditions in a compression ignition engine. (1st November 2021) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Fogué-Robles, Álvaro
Highlights: OMEx evaluated as single fuel under stoichiometric conditions. Stoichiometric OMEx combustion results in almost-zero soot emissions in all the range. Narrow lambda gap with EU VI emissions and engine better efficiency than diesel. Abstract: Low energy density fuels combined with low temperature combustion modes have demonstrated a great contribution to engine-out NOx and soot reduction. Additionally, synthetic fuels have become an important way of reaching carbon neutral utilization of hydrocarbon-based fuels and internal combustion engines. Specifically, poly-oxymethylene dimethyl ethers (OMEx) have demonstrated great advantages in combination with conventional fuels with higher energy content to compensate that aspect to reduce NOx emissions below the EU VI homologation normative while maintaining ultra-low soot emissions with a great benefit in CO2 emissions in a well-to-wheel basis. Nonetheless, the properties of this fuel in single-fuel combustion strategies are not thoroughly investigated in the literature. The objective of this work is to investigate the capabilities of OMEx fuel under conventional combustion modes compared to those of conventional diesel combustion. To do this, an experimental characterization under stoichiometric combustion has been carried out to evaluate the impact on engine hardware demand and total emissions. Additionally, a brief exploration under leaner conditions is performed. The results obtained from this work point out that, even under ultra-high EGR rates to reach high fuel-to-air ratios, OMEx fuel can emit ultra-low soot and NOx emissions with more than 90% reduction compared to diesel on engine out emissions. Under stoichiometric conditions, a significant increase appears on CO, UHC due to excessive usage of EGR and equivalent fuel consumption is penalized from 15% to 40% depending on the operating condition, but under slightly leaner conditions, a region where equivalent fuel consumption is improved with respect to CDC appears, and the four main pollutants investigated are almost EU VI compliant, exposing a very high potential for this fuel.